2010
DOI: 10.1073/pnas.0913373107
|View full text |Cite
|
Sign up to set email alerts
|

Spinal interneuron circuits reduce approximately 10-Hz movement discontinuities by phase cancellation

Abstract: Tremor imposes an important limit to the accuracy of fine movements in healthy individuals and can be a disabling feature of neurological disease. Voluntary slow finger movements are not smooth but are characterized by large discontinuities (i.e., steps) in the tremor frequency range (approximately 10 Hz). Previous studies have shown that these discontinuities are coherent with activity in the primary motor cortex (M1), but that other brain areas are probably also involved. We investigated the contribution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
81
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(86 citation statements)
references
References 48 publications
3
81
0
2
Order By: Relevance
“…Oscillations in the alpha (8)(9)(10)(11)(12) and beta (13-35 Hz) frequency band are commonly observed in recordings from the primary motor cortex [1]. Similar oscillations can also be detected in the electromyogram (EMG) of forearm and intrinsic hand muscles during sustained contraction.…”
Section: Introductionmentioning
confidence: 77%
“…Oscillations in the alpha (8)(9)(10)(11)(12) and beta (13-35 Hz) frequency band are commonly observed in recordings from the primary motor cortex [1]. Similar oscillations can also be detected in the electromyogram (EMG) of forearm and intrinsic hand muscles during sustained contraction.…”
Section: Introductionmentioning
confidence: 77%
“…However, this is quite unlikely as the stochastic nature of the noise makes it impossible to synchronize in antiphase the tremor oscillations. Another possible explanation for the better performance during ON is the suppression or reduction of the physiological tremor by supraspinal centers shown to be involved in the generation of 10 Hz tremor, such as the pontomedullary reticular formation and the deep cerebellar nuclei (Williams and Baker, 2009;Williams et al, 2010). These authors reported in monkeys that these supraspinal centers exhibit oscillations in neuronal activity at a tremor frequency occurring in antiphase with the oscillations generated by the spinal interneuron circuits.…”
Section: Possible Role Of the Physiological Tremormentioning
confidence: 87%
“…Similarly to the first issue discussed, this also implies that the secondary input may not be completely independent from the cortical inputs to the motoneuron pool, at least for the lower frequencies (approximately up to 10 Hz). The problem was investigated recently (Williams et al 2010;Tetzlaff et al 2010), and the results showed that an (inhibitory) feedback to a motoneuron pool can decrease the power of the oscillatory activity present in those frequency ranges and therefore affect the transmission of those frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…This interaction may act as neural filtering by suppressing or enhancing specific frequency components in the neural drive to muscles (motoneuron output) (Williams et al 2010). These mechanisms are relevant for force stability and may cause pathological conditions when the neural filtering is not fully effective, e.g., in pathological tremor (Halliday et al 1995;Raethjen et al 2009).…”
mentioning
confidence: 99%